“SINAR” Learning Innovation (Reasoning and Engineering Learning Model) - S. Suprihatin; I. Ismail (Manunggal Halim Jaya, 2026)
Learning in early childhood education needs to be conducted creatively and innovatively in order to foster children’s thinking abilities, curiosity, and problem-solving skills. One effort that can be implemented is through the innovation of Sinau and Nalar learning in kindergarten. This learning approach emphasizes activities that encourage children to think logically, explore, and discover knowledge through direct experiences. This study aims to examine how the Sinau and Nalar learning innovation is implemented and to identify its benefits for children’s cognitive development. The research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings show that the implementation of Sinau and Nalar learning can improve children’s critical thinking, creativity, and self-confidence in solving simple problems. Therefore, this learning innovation can serve as an effective alternative teaching strategy in kindergarten